1992
DOI: 10.1104/pp.98.3.827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of developmental gradients for growth, ATPase, and fusicoccin-binding activity in mung bean hypocotyls.

Abstract: A comparison has been made of the developmental gradients along a mung bean (Vigna radiata L.) hypocotyl of the growth rate, plasma membrane ATPase, and fusicoccin-binding protein (FCBP) activity to determine whether they are interrelated. The hook and four sequential 7.5 millimeter segments of the hypocotyl below the hook were cut. A plasma membrane-enriched fraction was isolated from each section by aqueous two-phase partitioning and assayed for vanadate-sensitive ATPase and FCBP activity. Each gradient had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
5
2
Order By: Relevance
“…Also, for mung beans, the absence of (or reduction in) K+-stimulation has been reported several times (Yoshidaetal. 1986, Kimuraet al 1988, Mitoetal, 1988, Basel and Cleland 1992, Tbis was confirmed by our own results (Tab, 1). The plasma membrane (U,) ATPase activity did not increase significantly in tbe presence of K*.…”
Section: Overall Purity Of Piasma Membranes Isolated From Mang Bean Hsupporting
confidence: 74%
See 1 more Smart Citation
“…Also, for mung beans, the absence of (or reduction in) K+-stimulation has been reported several times (Yoshidaetal. 1986, Kimuraet al 1988, Mitoetal, 1988, Basel and Cleland 1992, Tbis was confirmed by our own results (Tab, 1). The plasma membrane (U,) ATPase activity did not increase significantly in tbe presence of K*.…”
Section: Overall Purity Of Piasma Membranes Isolated From Mang Bean Hsupporting
confidence: 74%
“…The addition of vanadate and calcium to the assay medium caused a 35 to 40% inhibition of Mg-*-dependent ATPase activity. The VO^-inhibition was relatively small compared to inhibition rates for mung bean plasma membrane ATPases reported by others (Yoshida et al 1986, Basel andCleland 1992). Although vanadate inhibition was expected to be enhanced by the addition of K* to the medium (Widell and Larsson 1990), in the present experiments the level of inhibition was not drastically affected: K+ induced a supplementary reduction of only 5 to 10% (data not shown).…”
Section: Overall Purity Of Piasma Membranes Isolated From Mang Bean Hcontrasting
confidence: 57%
“…(1) all organs and developmental stages of the plant express the FCBP (Meyer et al, 1993); (2) expression of the FCBP is under developmental control (Base1 and Cleland, 1992;Meyer et al, 1993); and (3) the structure and biochemical properties of the FCBP are highly conserved in different plant species Weiler et al, 1990;Oecking and Weiler, 1991).…”
Section: Fcbp 1s the First 14-3-3 Homolog With A Receptor Functionmentioning
confidence: 99%
“…Binding activity in the plasma membrane is cell-type specific (Meyer et al, 1993) To whom correspondence should be addressed. and is controlled by the developmental stage of the tissue (Basel and Cleland, 1992). Modulation of the receptor affinity for FC by binding of its own ligand (Basel et al, 1994) further accentuates the role of the FCBP in the physiology of plants.…”
Section: Introductionmentioning
confidence: 97%
“…In situ , there is a gradient of elongation rate along the peel, i.e., elongation of portion I is fastest, while that of portion III is slowest (data not shown), but no significant differences in the rate of fusicoccin‐induced strain along peels were observed. Basel & Cleland (1992) found that the rate of fusicoccin‐induced growth in segments cut from mung bean hypocotyls does not correlate with endogenous growth rate of intact hypocotyls, although some gradients of growth rate exist in both cases. They concluded that endogenous growth rate is not determined by the activity of plasma membrane H + ‐ATPases.…”
Section: Discussionmentioning
confidence: 92%